1983
DOI: 10.1515/zna-1983-0814
|View full text |Cite
|
Sign up to set email alerts
|

On the Photodecomposition of ClONO2 in the Middle Ultraviolet

Abstract: Herrn Professor G. O. Schenck zu seinem 70. Geburtstag gewidmetPhotodecomposition of gaseous C10N0 2 was investigated in a static system at wavelengths 265 nm and 313 nm. From the quantitative determination of the products 0 2 , N 2 0 5 , and C10 l5 N0-> formed, and from <£(-C10N0 2 ) it is concluded that the predominant primary step is C10NÖ 2 + h v CI + N0 3 (3).Chlorine nitrate, C10N0 2 , is considered to be formed in the stratosphere via the pressure dependent recombination reaction C10 + N0 2 + N 2^ C10N0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although the ClO−NO 2 bond is the weakest in ClONO 2 , initial experimental studies reported that the ClO + NO 2 channel was only of minor importance. Knauth and Schindler reported that channel (3) was the dominant dissociation channel at 265 and 313 nm in a static cell . Margitan observed that Cl and O atoms were the two major products with quantum yields of 0.9 and 0.1 respectively at 266 and 355 nm using the atomic resonance fluorescence detection method .…”
Section: Introductionmentioning
confidence: 99%
“…Although the ClO−NO 2 bond is the weakest in ClONO 2 , initial experimental studies reported that the ClO + NO 2 channel was only of minor importance. Knauth and Schindler reported that channel (3) was the dominant dissociation channel at 265 and 313 nm in a static cell . Margitan observed that Cl and O atoms were the two major products with quantum yields of 0.9 and 0.1 respectively at 266 and 355 nm using the atomic resonance fluorescence detection method .…”
Section: Introductionmentioning
confidence: 99%
“…The direct study by Marindli and Johnston (8) found that the NO, yield, corrected for a revised calibration factor (1 I), is less than 40%, and NO, and secondary N20, products have been detected in steady state (11) and static cell (5,9) experiments. 26.…”
mentioning
confidence: 99%